2021
DOI: 10.3390/ijerph18020707
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intimate Partner Violence in Pregnancy: An Umbrella Review

Abstract: Background: Intimate partner violence (IPV) is a public health concern, especially during pregnancy, and needs to be urgently addressed. In order to establish effective actions for the prevention of IPV during pregnancy, authorities must be aware of the real burden of IPV. This review aimed to summarize the existing evidence about IPV prevalence during pregnancy worldwide. Methods: A review of reviews was carried out. All published systematic reviews and meta-analyses published until October 2020 were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 35 publications
0
35
1
Order By: Relevance
“…A published systematic review and meta-analysis gave a low quality prevalence of IPV as 1.6-78% physical abuse and psychological type as 1.8-67.4%. These results were contradictory to the present results as verbal abuse was among the highest reported type of the violence [6].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A published systematic review and meta-analysis gave a low quality prevalence of IPV as 1.6-78% physical abuse and psychological type as 1.8-67.4%. These results were contradictory to the present results as verbal abuse was among the highest reported type of the violence [6].…”
Section: Discussioncontrasting
confidence: 99%
“…Although these were recent reviews but of low quality with AMSTAR2 recommendations and without capturing the total global burden of the disease under discussion. These showed only one out of two and one of 50 females suffer physical and psychological violence [6].…”
Section: Intimate Partner Violence Has Been Researched In Pakistanmentioning
confidence: 98%
“…An umbrella review of collated summaries of the published worldwide and country IPV prevalence data in pregnancy (13) showed that the existing evidence syntheses did not capture the totality of the disease burden, they did not always specify the gestational time point of IPV evaluation, and sometimes the IPV and domestic violence concepts were mixed up, leaving ambiguity. When assessed for quality, the existing reviews showed possible bias in study selection, general failure in addressing heterogeneity, and a narrow geographical coverage, focused on low-income countries (13). A robust updated systematic review of IPV prevalence in pregnancy is required to provide underpinning evidence for antenatal care policies.…”
Section: Introductionmentioning
confidence: 99%
“…The combination may have an inter-generational impact on her infant. Around 28% of pregnant women experience physical or sexual IPV during pregnancy [5] and a recent umbrella review of 12 studies found that emotional p-IPV can be wide ranging, with between 1.8 to 67.4% [6]. p-IPV is also associated with a range of adverse perinatal outcomes, such as miscarriages and pre-term births [7].…”
Section: Introductionmentioning
confidence: 99%